1993
DOI: 10.3109/10425179309020839
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral-like features in the monomer of the major satellite DNA from the South American rodents of the genus Ctenomys

Abstract: It is well known that uninfected mammalian cells contain DNA sequences which are closely related to retroviral genomic segments. However, these sequences seldom (if ever) have been found associated to highly repetitive (satellite) DNA. RPCS is a 348 bp monomer of a major satellite DNA from the South American rodents of the genus Ctenomys. It was found that RPCS contains several elements which are typical of the U3 region of retroviral LTRs. These elements are: a) a polypurine tract; b) two enhancer core sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Similarity between MSAT-160 and the RPCS satellite from the South American rodent Ctenomys (Rossi et al, 1993) was found, and these two DNA sequences were aligned. The IR ele ments of MSAT-160 have similarity to two pairs of IRs located in the terminal and central regions of RPCS, viz., the reported 348-bp repeat unit appears to be a dimer consisting of two unre lated subunits of approximately equal length (Fig.…”
Section: Comparison O F Msat-160 With Other Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarity between MSAT-160 and the RPCS satellite from the South American rodent Ctenomys (Rossi et al, 1993) was found, and these two DNA sequences were aligned. The IR ele ments of MSAT-160 have similarity to two pairs of IRs located in the terminal and central regions of RPCS, viz., the reported 348-bp repeat unit appears to be a dimer consisting of two unre lated subunits of approximately equal length (Fig.…”
Section: Comparison O F Msat-160 With Other Sequencesmentioning
confidence: 99%
“…This 14-bp motif immediately precedes the start of MSAT-21 and reveals that the terminal (or junction) monomer of MSAT-160 is full length, as is the first (or junction) mono mer of MSAT-21; i.e., no deletions in either satellite or inser tions of foreign DNA exist at the junction. The only unusual Rossi et al (1993).…”
Section: The Junction Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major satellite DNA of tuco-tucos, named RPCS (repetitive PuvII Ctenomys sequence), is organized in long arrays of 348 bp monomer units (Novello et al 1988;Rossi et al 1990). In situ hybridization showed that RPCS mainly localizes in different chromosomal regions positive for C-banding: whole arms and pericentromeric blocks, as well as telomeric and interstitial bands (Rossi et al 1993;Novello et al 1996) in mitotic and meiotic cells (Novello and Villar 2006).…”
Section: Introductionmentioning
confidence: 99%